Arturo O. answered • 12/18/17

Tutor

5.0
(66)
Experienced Physics Teacher for Physics Tutoring

I will set this up for you and you work the math.

f(n) = f(n - 1) + 3

n = 7

f(7) = f(7 - 1) + 3 = f(6) + 3

Do the same for f(6).

f(6) = f(5) + 3 ⇒

f(7) = f(5) + 3 + 3

Similarly,

f(5) = f(4) + 3 ⇒

f(7) = f(4) + 3 + 3 +3

Do you see the pattern emerging here? Keep going until you are down to

f(2) = f(1) + 3 = 6 + 3 = 9

Then carefully plug the intermediate answers into their proper place in

f(7) = f(6) + 3